Preparation of 2,6-Naphthalic Acid by Liquid Phase Oxidation of 2,6-Diisopropyl Naphthalene - Peng, Ge (Asian Journal of Chemistry, 2012)
An orthogonal experiment was carried out and the effects of bromine, metal ions additives and organic nitrogen compounds on the yield of 2,6-naphthalic acid were discussed. The results shown that influence order for the yield of 2,6-naphthalic acid in the orthogonal experiment were: reaction temperature > feed flux > catalyst dosage > Co/Mn. High temperature could cause the cleavage of naphthalene ring and low temperature could not give rise to the full oxidation of intermediate products, then the suitable temperature could be 473 K. It is good for producing 2,6-naphthalic acid to decrease the feed flux and increase the catalyst dosage. However, there was no significant influence of Co/Mn for the yield of 2,6-naphthalic acid.